Territorialized Social Movements: The Maghreb, From The Margins To The Center The Case Of The Hirak Rif Movement - Imane Errami; Chaimae Chinig (The Journal of Studies in Language, Culture and Society, 2021)
Starting from a long-term ethnographic survey (2016-2019) on the "Hirak Rif" movement, this article questions the modalities of politicization of marginalized communities. Located in the north of Morocco,On October 28, 2016 in Al-Hoceïma, Mohcine Fikri died crushed in a dumpster while trying to recover the merchandise that had been confiscated by the authorities. The 31-year-old was a fish merchant. He was accused of being in possession of nearly 500 kg of swordfish, which was banned from fishing during this period. He was killed opposing the destruction of his cargo in a dumpster.His death was the starting point for the protest in the Rif. It is a region of northern Morocco whose history is marked by the repression and marginalization it suffered during the reign of Hassan II.Then the events of 1958-1959, followed by the issuance of a military dahir to make Al Hoceima a military region, and the unrest of 1984 and the disturbances of 1984 and called the Rif people a slogan (awbash) in an official letter from the late King Hassan II, and all these elements reflect the state of the rift between the region and the central authority continuing until today that the era of reconciliation could not erase it. Rif residents agree that the reconciliation experience did not succeed in folding the countryside file in a way that amounts to reconciliation, where memory and history have been surpassed, until 2016, many Rif youth were arrested, the emigration of others and accusing the population of seeking separation and “work” abroad these concepts are consistent with the historical concept that was described by the region before independence” bled Siba”; what this means is that the Rif protest practice Identity memory practice, governed by social frameworks. This was observed through the presence of the Amazigh flag (Tamazgha) and the flag of the countryside of the countryside (Bandu Nereef), and the adoption of a discourse based on the principles of local and regional identities: common language (Tarifit), race, and collective history: Muhammad bin Abdul Karim al-Khattabi)and the slogans he raised The demonstrators. In addition to "pledging allegiance to the protests," Whenever the population of the Rif contests the policy of power, the Makhzen responds with violence and marginalization of the region, thus preparing the conditions for a new cycle of protest and repression. This in fact explains, to a large extent, the motive behind choosing the subject of this study, it appears that focusing on the historical factor is also very important to understand of the protests and to move away from interpretations one-dimensional focusing on economic and social dimensions only. The objective of this article is to include the study of the mobilizations of marginalized communities in a more global sociological analysis.